2005
DOI: 10.1002/ajhb.20464
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, seasonal body fat, heart rate, and ecological differences in Caboclo populations of the Brazilian Amazon

Abstract: This study compares blood pressure (BP) and related cardiovascular risk factors among three Caboclo communities from the Brazilian Amazon. Its purpose is to investigate possible risk differentials related to variable ecological settings and Western influences. Caxiuanã is characterized as a more "traditional" group, while Aracampina and Santana are viewed as more "transitional" in lifestyle. A total of 348 subjects from the three communities were evaluated in the wet or the dry season or in both. Measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Other information about the ecologic situation, history, geography, social and economic conditions, subsistence and health aspects of the groups and investigated areas are available in previous publications (Borges, 2011;Cavalcante, 2011;Filgueiras and Silva, 2013;Guimarães and Silva, 2015;Lisboa et al, 2013;Melo and Silva, 2015;Moura, 2007Moura, , 2008; Moura et al, 2016;Pinho et al, 2013;Piperata and Dufour, 2007;Piperata et al, 2011Piperata et al, , 2013Silva, 2002Silva, , 2009Silva, , 2011Silva and Padez, 2010;Silva et al, 2006;Silveira et al, 2013).…”
Section: Research Location and Populationsmentioning
confidence: 99%
“…Other information about the ecologic situation, history, geography, social and economic conditions, subsistence and health aspects of the groups and investigated areas are available in previous publications (Borges, 2011;Cavalcante, 2011;Filgueiras and Silva, 2013;Guimarães and Silva, 2015;Lisboa et al, 2013;Melo and Silva, 2015;Moura, 2007Moura, , 2008; Moura et al, 2016;Pinho et al, 2013;Piperata and Dufour, 2007;Piperata et al, 2011Piperata et al, , 2013Silva, 2002Silva, , 2009Silva, , 2011Silva and Padez, 2010;Silva et al, 2006;Silveira et al, 2013).…”
Section: Research Location and Populationsmentioning
confidence: 99%
“…As in the past, rural Ribeirinho populations continue to practice subsistence agriculture (Brondizio and Siquiera, 1997;Murrieta et al, 1999;Piperata and Dufour, 2007;Piperata, 2007) but are also intimately linked to the regional market economy with their level of integration related to market demand for local products or the temporary availability of wage-earning opportunities. Despite their demographic dominance, Ribeirinhos have received relatively little attention in the literature and, with the exception of a handful of studies (Giugliano et al, 1981(Giugliano et al, , 1984Silva et al, 1995Silva et al, , 2006Silva et al, , 2010Murrieta et al, 1998;Piperata and Dufour, 2007;Piperata, 2007), very little is known about their health, especially as it relates to rapidly changing circumstances in this highly dynamic setting.…”
Section: Economic Change and Market Integration Among Ribeirinhosmentioning
confidence: 99%
“…Contemporary research on food consumption among indigenous peasants, also called caboclos or ribeirinhos (Moran 1974(Moran , 1991Parker 1985, for a recent debate see Adams et al 2006), have identified several patterns which may be generalized to the whole region: heavy dependence on regional staple food items (e.g., manioc and fish); increasing dependence on commercial and/or imported products; high protein consumption relative to calories; high seasonal variety of secondary food items; and the possible appearance of an epidemic pattern, characterized by the overlap of moderate states of malnutrition and chronic diseases related to changes in food habit and activity level (e.g., obesity and diabetes, among others) (Adams 2002;Adams et al 2005;Giugliano et al 1981Giugliano et al , 1984Murrieta and Dufour 2004;Murrieta et al 1999Murrieta et al , 2004Murrieta 1998Murrieta , 1999Rocha et al 1993;Silva et al 2006). Additional factors have influenced food consumption patterns over the last three decades in Amazonia, including the explosive growth of urban areas promoted at least partially by the decline of traditional subsistence activities such as extraction of forest products (e.g., rubber, gums, and fibers) and shifting cultivation (manioc), as well as by the intensification of commercial large-scale fishing and logging elsewhere (McGrath et al 1993;Padoch et al 1999).…”
Section: Introductionmentioning
confidence: 97%